Normal stress difference-driven particle focusing in nanoparticle colloidal dispersion - Kim, Bookun; Lee, Sung Sik; Yoo, Tae Hyeon; Kim, Sunhyung; Kim, So Youn; Choi, Soo Hyung; Kim, Ju Min (Science Advances, 2019)
Colloidal dispersion has elastic properties due to Brownian relaxation process. However, experimental evidence for the elastic properties, characterized with normal stress differences, is elusive in shearing colloidal dispersion, particularly at low Péclet numbers (Pe < 1). Here, we report that single micrometer-sized polystyrene (PS) beads, suspended in silica nanoparticle dispersion (8 nm radius; 22%, v/v), laterally migrate and form a tightly focused stream by the normal stress differences, generated in pressure-driven microtube flow at low Pe. The nanoparticle dispersion was expected to behave as a Newtonian fluid because of its ultrashort relaxation time (2 ms), but large shear strain experienced by the PS beads causes the notable non-Newtonian behavior. We demonstrate that the unique rheological properties of the nanoparticle dispersion generate the secondary flow in perpendicular to mainstream in a noncircular conduit, and the elastic properties of blood plasma-constituting protein solutions are elucidated by the colloidal dynamics of protein molecules.
Keywords: Brownian relaxations; Colloidal dispersion; Elastic properties; Experimental evidence; Nano-particle dispersions; Non-Newtonian behaviors; Normal stress difference; Rheological property